METAGENOMIC ANALYSIS OF THE STRUCTURE OF THE BACTERIAL COMMUNITY OF THE TEREN-UZEK DEPOSIT (Experimental biology, 2025)
Determining the microbial profile and physicochemical conditions of low-yield oil reservoirs is a key prerequisite for the implementation of cost-effective biotechnologies aimed at recovering hard-to-extract oil from water-flooded wells. The aim of this study was to assess the microbial and physicochemical profile of water-flooded oil reservoirs at the "Teren-Uzek" oil field using metagenomic analysis. The study involved physicochemical measurements of formation water samples and high-throughput sequencing of 16S rRNA genes to determine the taxonomic composition of the microbial community. It was found that the high salinity of the formation water, with an extremely saline environment at depths of 800–850 meters and a temperature of 21 °C, creates unique conditions for the survival of microorganisms adapted to such environments. The microbiota of the water-flooded oil reservoirs was found to be represented exclusively by the domain Bacteria and, at the phylum level, was mainly composed of members of Actinobacteria and Proteobacteria. The microbial community demonstrated low taxonomic diversity at the class level, with dominance of Actinobacteria and Gammaproteobacteria. The majority of the bacterial community consisted of representatives of the genera Dietzia (39.67%) and Halomonas (35.17%), together accounting for over 74% of the total identified sequences. Other genera were present in smaller proportions, including Janibacter (3.21%), Bacillus (2.12%), Georgenia (2.11%), Arthrobacter (2.01%), and Marinobacter (1.38%). The specific conditions of these oil reservoirs suggest the potential applicability of indigenous microorganisms, and the identified taxa are of interest for further exploration in the development of biotechnological approaches aimed at enhanced oil recovery (MEOR) and biodegradation of contaminating compounds.
Keywords: Petroplast, microflora, microbiological status, extreme conditions.